2021
DOI: 10.1002/rmb2.12421
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of chronic endometritis in different types of human adenomyosis

Abstract: Purpose Human adenomyosis has an adverse effect on female fertility. Exact mechanistic basis is still unclear. We investigated the occurrence of chronic endometritis (CE) in different types of human adenomyosis. Methods This is a prospective non‐randomized observational study enrolling patients with focal ( n = 30), diffuse ( n = 26), intrinsic ( n = 23), and extrinsic ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…A number of epidemiological studies have shown that both a history of uterine surgery and multiple births are risk factors for AM [24][25][26]. Another study has suggested macrophage in ltration in the endometrium may be signi cantly higher in intrinsic AM than in extrinsic AM [27]. Our study found that the education level of the patients, gravidity, and number of endometrial curettage are all factors closely related to intrinsic AM.…”
Section: Discussionsupporting
confidence: 59%
“…A number of epidemiological studies have shown that both a history of uterine surgery and multiple births are risk factors for AM [24][25][26]. Another study has suggested macrophage in ltration in the endometrium may be signi cantly higher in intrinsic AM than in extrinsic AM [27]. Our study found that the education level of the patients, gravidity, and number of endometrial curettage are all factors closely related to intrinsic AM.…”
Section: Discussionsupporting
confidence: 59%
“…These findings suggest that the eutopic endometria of patients with adenomyosis are recognized as a low-grade inflammatory state due to overexpression of TLRs and that a different expression spectrum of the upper genital tract microbiota may be implicated in disease development. Indeed, the incidence of chronic endometritis was higher in women with adenomyosis (approximately 60%) compared to control women (10%) [ 115 ]. Dysbiosis of endometrial microbiota may promote adenomyosis risk, possibly through an aberrant expression of inflammatory cytokines and chemokines ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…(iii) Impairment of implantation may result from inflammation, a lack of adequate expression of adhesion molecules (integrins), reduced expression of implantation markers, such as leukemia inhibitory factor (LIF), and altered function of the gene for embryonic development (HOXA10) [ 185 ]. (iv) Occurrence of chronic endometritis (CE) resulting from intrauterine microbial infection may be associated with negative fertility outcome in women with adenomyosis [ 186 ].…”
Section: Association With Infertilitymentioning
confidence: 99%
“…A recent study provides the first piece of clinical evidence that a variable rate of chronic endometritis (CE) occurs in women with different types of adenomyosis, such as focal and diffuse adenomyosis [ 192 ]. Although an insignificant difference in the occurrence of CE was found between focal (58.8%) and diffuse adenomyosis (60.0%), the ipsilateral side of focal adenomyosis showed a significantly higher occurrence of CE (58.8%) than the contralateral side (11.7%) [ 186 ]. These findings indicated that a variable occurrence of CE in different types of adenomyosis may be involved in negative fertility outcome.…”
Section: Association With Infertilitymentioning
confidence: 99%